Exposure to arsenic and cognitive impairment in children: A systematic review - Yumei Tian; Qi Hou; Mingyue Zhang; Er Gao; Yue Wu (PLoS ONE, 2025)
Objective Arsenic exposure is a significant public health concern, particularly for its impact on children’s cognitive development. Arsenic, a prevalent environmental toxin, is known to disrupt various biological pathways, leading to cognitive deficits and neurodevelopmental issues. Understanding the long-term effects and mechanisms underlying arsenic-induced cognitive impairments is crucial for devising effective interventions. Methods This systematic review included observational and experimental studies focusing on children under 18 years exposed to arsenic through drinking water, food, or other environmental sources. Studies were selected through comprehensive database searches, encompassing articles that measured cognitive outcomes via standardized tests. The synthesis was primarily narrative, given the heterogeneity in study designs, exposure levels, and outcomes. Results The review analysed findings from 24 studies, showing a consistent inverse relationship between arsenic exposure and cognitive performance in children. Higher arsenic levels were associated with lower IQ scores, slower processing speeds, and impaired memory and language skills. These cognitive deficits were evident across diverse geographical regions and persisted even after adjusting for sociodemographic factors. The studies highlighted the potential for both immediate and long-term cognitive effects, underscoring the importance of early-life exposure. Conclusions Arsenic exposure has the potential to impair cognitive development in children. Nonetheless, quantitative meta-analysis is necessary to deduce any conclusions related to its impact. Public health efforts must prioritize reducing arsenic exposure through improved water quality and community-awareness programs. Future research should focus on longitudinal studies to better understand the dose-response relationship and the effectiveness of intervention strategies. Systematic review registration Prospero, CRD42024544442.